Managing the Energy Price Crisis in Lithuania: From Operational Responses to Policy Change - Kalanta, Marius (Politologija, 2025)
The paper examines government responses to the recent energy price crisis in the context of the polycrisis in Lithuania. It adopts a framework which links these responses to the response paradigm followed by the government comprised of two layers: the crisis management paradigm, and the policy paradigm specific to a policy field. The paper explores how these two layers evolved in the energy sector given the polycrisis and historical contexts, and how they interacted in shaping the operational and strategic policy responses to the energy crisis. The paper shows that, to manage the crisis, the government adopted a paradigm based on activist state intervention and principles of fast and simple horizontal relief measures for households and businesses, which is an approach that proved effective during the earlier coronavirus pandemic. In addition, the crisis management paradigm had a clear strategic component in the form of price and investment incentives for the more aggressive expansion of domestic renewable energy sources-based energy generation capacities. While favourable conditions for this strategic component came from EU-wide attempts to cope with the climate crisis, the paper also links it to an energy crisis-provoked shift in the energy policy paradigm among Lithuanian political leaders, which altered the way energy security is perceived. If, prior to the crisis, energy security was mainly perceived as a redirection of energy flows from Russia to the EU, during and after the crisis it started to be increasingly viewed as full energy independence, achieved through the technological transformation of the whole energy system.
Keywords: energy security; energy price crisis; polycrisis; energy transition; policy change; crisis managment; Lithuania